Pentraxin 3 in Noninvasively Obtained Cervical Fluid Samples from Pregnancies Complicated by Preterm Prelabor Rupture of Membranes - Janku, Petr; Kacerovsky, Marian; Zednikova, Barbora; Andrys, Ctirad; Kolackova, Martina; Drahosova, Marcela; Pliskova, Lenka; Zemlickova, Helena; Gerychova, Romana; Simetka, Ondrej; Matlak, Petr; Jacobsson, Bo; et al. (Fetal diagnosis and therapy, 2019)
PROBLEM: To determine the changes of pentraxin 3 (PTX3) level in noninvasively obtained cervical fluid samples from women with preterm prelabor rupture of membranes (PPROM) based on the presence of microbial invasion of the amniotic cavity (MIAC) and/or intra-amniotic inflammation (IAI), and intra-amniotic infection (the presence of both MIAC and IAI). METHODS OF STUDY: A total of 160 women with PPROM were included. Cervical fluid samples were obtained using a Dacron polyester swab and amniotic fluid samples were obtained by transabdominal amniocentesis. Cervical fluid PTX3 levels were assessed using enzyme-linked immunosorbent assay. RESULTS: PTX3 was found in all the cervical fluid samples and its levels were higher in women with MIAC, IAI, and intra-amniotic infection than in women without these conditions. When the women were categorized into four subgroups based on the presence of MIAC and/or IAI, women with intra-amniotic infection had higher cervical fluid PTX3 levels than those with sterile IAI (IAI alone), colonization (MIAC alone), or no MIAC or IAI. A cervical fluid PTX3 level of 11 ng/mL was the best value for identifying the presence of intra-amniotic infection in women with PPROM. CONCLUSIONS: PTX3 is a constituent of cervical fluid of women with PPROM. Cervical fluid PTX3 level reflects the situation in the intra-amniotic compartments of women with PPROM. Cervical fluid PTX3 is a potential marker for the noninvasive identification of intra-amniotic infection in PPROM.
Keywords: Enzyme-Linked Immunosorbent Assay; chorioamnionitida; Chorioamnionitis; Female; předčasný odtok plodové vody; biologické markery; C-Reactive Protein; Biomarkers; ženské pohlaví; Up-Regulation; cervix uteri; Predictive Value of Tests; prediktivní hodnota testů; lidé; těhotenství; Pattern recognition receptor; upregulace; sérový amyloidový protein; Fetal Membranes, Premature Rupture; Inflammation; retrospektivní studie; ELISA; Amniotic Fluid; plodová voda; Serum Amyloid P-Component; Preterm birth; C-reaktivní protein; Pregnancy; Cervix Uteri; Retrospective Studies; Microorganism; Humans